Layered column type covalent organic framework material and preparation method thereof

By introducing column support molecules into two-dimensional covalent organic frame materials, the three-dimensional layer column structure is constructed, which solves the stacking effect problem caused by narrow interlayer spacing, and significantly improves the crystallinity, active site exposure and catalytic performance of the material.

CN119842090AActive Publication Date: 2025-04-18YUNNAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510085814.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-18
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

In practical applications, two-dimensional covalent organic frame materials (COFs) are narrowed between layers due to the strong π-π interaction between layers, resulting in severe stacking effects, shielding active sites, reducing effective surface area, and affecting the selectivity and current density of the catalyst.

Method used

By introducing columnar molecules such as pyrazine (Pz), bipyridine (Bp) or terephthalic acid (TPA), we construct three-dimensional columnar COFs materials, and adjust the length of the "column molecules" to accurately regulate the interlayer spacing, thereby optimizing material performance.

Benefits of technology

The crystallinity and layer spacing of COFs are significantly improved, the exposure of active sites is enhanced, specific surface area and structural stability is improved, and the catalytic performance is significantly improved, especially in electrochemical activity and CO2 to CO conversion selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842090A_ABST
    Figure CN119842090A_ABST
Patent Text Reader

Abstract

The invention discloses a layered column type covalent organic framework material and a preparation method thereof, and belongs to the field of high polymer materials. The invention provides a layered column type covalent organic framework material which is prepared by taking 5, 10, 15, 20-tetra (4-aminobenzene) porphyrin-M or 5, 10, 15, 20-tetra (4-aldehyde phenyl) porphyrin-M and aromatic dialdehyde / amine as raw materials and combining pillared molecules under the action of a Lewis acid catalyst (trifluoromethanesulfonic acid metal salt). According to the invention, a three-dimensional layer column type structure is constructed by introducing pillared molecules into framework layers, so that the material has excellent electrochemical activity and high-selectivity CO2 reduction performance, and shows an ideal application prospect in electro-catalysis CO2-CO conversion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of covalent organic frameworks (COFs) materials, and specifically relates to a layered pillar type COFs material with pyrazine (Pz), bipyridine (Bp) and terephthalic acid (TPA) as pillar molecules and a preparation method thereof. Background Art

[0002] COFs are a class of crystalline porous materials formed by dynamic covalent bond assembly of organic ligands. They have attracted widespread attention in the fields of catalysis, gas storage, separation and sensors due to their structural tunability, high specific surface area and abundant active sites.

[0003] With the overuse of fossil fuels and the greenhouse gas CO 2 Due to the large-scale emission of CO2, the world is facing severe environmental and energy challenges. COFs have become ideal materials for electrocatalytic carbon dioxide reduction reactions due to their unique high specific surface area, high porosity and structural adjustability. However, two-dimensional (2D) COFs still face difficulties in practical applications. Specifically, due to the strong π-π interaction between the layers, the interlayer spacing is usually narrow (usually less than 0.5nm), resulting in a serious stacking effect. This stacking effect not only shields the active sites and reduces the effective surface area, but also significantly affects the selectivity and current density of the catalyst.

[0004] There are two ways to solve the above problems. One is to prepare single-layer or multi-layer COFs to fully expose the catalytic center and enhance the catalytic activity. The other is to introduce "pillar molecules" into the COFs interlayer to reduce the stacking effect by expanding the interlayer spacing, thereby optimizing the material performance. Summary of the invention

[0005] The present invention provides a method for preparing a layered pillar type covalent organic framework material, which improves the crystallinity and interlayer spacing of COFs while avoiding substantial modification of the original structure. The material prepared by the method can be widely used in the field of electrocatalytic carbon dioxide reduction.

[0006] A layered columnar covalent organic framework material, the structural formula is as follows:

[0007]

[0008] Wherein, X or Y is C or N, and X and Y are different;

[0009] M is a transition metal;

[0010] for

[0011] Ar or Ar' is one of the following:

[0012]

[0013] R is an alkyl group or an alkoxy group;

[0014] The M-Por is TAPP or TFPP.

[0015] The transition metal is Co, Fe or Cu.

[0016] The alkyl or alkoxy group is H, CH з , C 2 H 5 , OH or OMe.

[0017] A method for preparing a layered pillar type covalent organic framework material, characterized in that the method comprises the following steps:

[0018] Step 1, M-Por, aromatic dialdehyde or aromatic diamine, and pillaring molecules are mixed at a molar ratio of 1:2:1-2 to make the concentration of M-Por 0.05M, and then n-butanol and o-dichlorobenzene are added, and after ultrasonic dispersion, a catalyst is added;

[0019] Step 2, the mixed system of step 1 is sequentially frozen with liquid nitrogen, vacuumed and degassed, and then the system is sealed to obtain a crude product;

[0020] Step 3, the crude product is filtered, washed, Soxhlet extracted and vacuum dried to obtain a columnar covalent organic framework material.

[0021] The catalyst is Lewis acid, namely trifluoromethanesulfonic acid metal salt, including scandium trifluoromethanesulfonate, zinc trifluoromethanesulfonate, iron trifluoromethanesulfonate, yttrium trifluoromethanesulfonate and indium trifluoromethanesulfonate, and the concentration thereof is 0.09-0.3 mol / L.

[0022] The volume ratio of the n-butanol to o-dichlorobenzene mixture is 1:1.

[0023] The crude product was washed by filtration with water and acetone, extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively, and dried under vacuum at 65° C. for 12 hours to obtain a columnar covalent organic framework material.

[0024] The present invention provides a new method for constructing three-dimensional layer-column COFs materials by introducing pillar molecules containing pyridine nitrogen or carboxyl groups, such as pyrazine Pz, bipyridine Bp, terephthalic acid TPA, etc., into two-dimensional COFs. This method significantly improves the crystallinity and interlayer spacing of COFs while avoiding major modifications to the original structure. By adjusting the length of the "pillaring molecule", the interlayer spacing can be precisely controlled, thereby further optimizing the material performance, providing a new technical path for its application in the electrocatalytic carbon dioxide reduction reaction.

[0025] The frame material of the present invention has the following significant advantages:

[0026] 1. Optimization of crystallinity and interlayer spacing: Effectively improve the crystallinity and interlayer spacing of COFs while avoiding significant changes to the monomer structure.

[0027] 2. Adjustable interlayer spacing: By adjusting the length of the "pillar supporting molecules", the interlayer spacing can be precisely controlled to optimize the framework performance.

[0028] 3. Enhancement of active sites: Significantly improve the exposure of active sites, improve the quality of guest molecules, and the diffusion channels of ions and electrons.

[0029] 4. Electronic and pore regulation: Modulate the electronic properties of COFs and catalytic centers, and fine-tune the porosity to increase the specific surface area and improve structural stability.

[0030] 5. Excellent catalytic performance: The material has excellent electrochemical activity and CO 2 It exhibits excellent performance in the conversion selectivity to CO, demonstrating its broad application prospects in the field of carbon dioxide electrocatalytic reduction. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The figure is a flow chart for preparing the layered columnar covalent organic framework of the present invention.

[0032] Figure 2 This is the powder X-ray diffraction pattern of the two-dimensional covalent organic framework - COF-366-Co; 3.50, 4.15, and 7.2 degrees are the characteristic peaks of the material, the strongest peak is located at 3.50 degrees, and the diffraction intensity is about 1130.

[0033] Figure 3 The powder X-ray diffraction pattern of the layered columnar covalent organic framework-COF-366-Co-Pz prepared by the present invention;

[0034] Figure (a) shows Pz of 1.2eq, and Figure (b) shows Pz of 2.0eq; 3.44, 4.17, 6.88 and 8.38 degrees are characteristic peaks of the material, and the strongest peak is located at 3.44 degrees, with a diffraction intensity of about 1300, slightly higher than COF-366-Co (1130); but when the equivalent of Pz increases, the crystallinity decreases; when the equivalent of Pz is 2eq, its strongest peak diffraction intensity is about 1090, which is close to the strongest peak diffraction intensity of COF-366-Co (1130).

[0035] Figure 4 (a) is the powder X-ray diffraction pattern of a covalent organic framework - Bpy CoTPP-DMTP-COF with a similar structure prepared by the preparation method reported in the literature, Figure 4 (b) is the powder X-ray diffraction pattern of the covalent organic framework-CoTPP-DMTP-COF without the introduction of Bpy (Bpy=Bp);

[0036] It can be clearly seen from the figure that the covalent organic framework - BpyCoTPP-DMTP-COF prepared by introducing Bpy using the method reported in the literature has a significantly decreased crystallinity compared to the covalent organic framework - CoTPP-DMTP-COF without the introduction of Bpy; the literature is Xie SL, Liu RY, Liu NY, et al. Vertically Expanded Covalent Organic Frameworks for Photocatalytic Water Oxidation into Oxygen. Angew Chem Int Edit. Nov 19 2024.

[0037] Figure 5 The powder X-ray diffraction pattern of the layered columnar covalent organic framework-COF-366-Co-Bp prepared by the present invention;

[0038] In Figure (a), Bp is 1.2eq, and in Figure (b), Bp is 3.0eq; 3.48, 4.01, 6.96 and 10.09 degrees are characteristic peaks of the material, and the strongest peak is located at 3.48 degrees, with a diffraction intensity of about 3004, which is much higher than COF-366-Co (1130); but when the equivalent of Bp increases, its crystallinity also decreases; when the equivalent of Bp is 3eq, its strongest peak diffraction intensity is about 956, which is lower than the strongest peak diffraction intensity of COF-366-Co (1130).

[0039] Figure 6 The nitrogen adsorption-desorption curve (a) and pore size distribution diagram (b) of the two-dimensional covalent organic framework-COF-366-Co;

[0040] Its adsorption-desorption curve is a type I isotherm curve, indicating that its structure is a microporous structure. The calculated specific surface area of ​​the material is 1055m 2 g -1 According to the pore size distribution diagram, the pore size is mainly distributed at 1.95 nm, and the cumulative pore volume is 0.374 cm 3 / g.

[0041] Figure 7 The nitrogen adsorption-desorption curve (a) and pore size distribution diagram (b) of the layered pillar type covalent organic framework -COF-366-Co-Pz (1.2eq) prepared by the present invention;

[0042] The adsorption-desorption curve of COF-366-Co-Pz (1.2 eq) is a type I isotherm, indicating that its structure is a microporous structure. The specific surface area of ​​the material is calculated to be 1970 m 2 g -1 , much higher than the specific surface area of ​​COF-366-Co (1055m 2 g -1 ); According to the pore size distribution diagram, the pore sizes are mainly distributed at 1.24 nm and 1.78 nm, and the cumulative pore volume is 0.741 cm 3 / g; it is also much higher than the cumulative pore volume of COF-366-Co (0.374 cm 3 / g).

[0043] Figure 8 The nitrogen adsorption-desorption curve (a) and pore size distribution diagram (b) of the covalent organic framework-Bpy CoTPP-DMTP-COF with similar structure prepared by the preparation method reported in the literature and the nitrogen adsorption-desorption curve (c) and pore size distribution diagram (d) of the covalent organic framework-CoTPP-DMTP-COF without the introduction of Bpy;

[0044] The figure shows that after introducing Bpy according to the preparation method of the literature, the specific surface area and cumulative pore volume of the covalent organic framework-Bpy CoTPP-DMTP-COF are lower than the specific surface area and cumulative pore volume of the covalent organic framework-CoTPP-DMTP-COF without introducing Bpy; while the specific surface area and cumulative pore volume of CoTPP-DMTP-COF are lower than the specific surface area and cumulative pore volume of COF-366-Co; the literature is referred to as: Xie SL, Liu RY, Liu NY, et al. Vertically Expanded Covalent Organic Frameworks for Photocatalytic Water Oxidation into Oxygen. Angew Chem Int Edit. Nov 19 2024.

[0045] Fig. 9 The nitrogen adsorption-desorption curve (a) and pore size distribution diagram (b) of the layered columnar covalent organic framework-COF-366-Co-Bp (1.2 eq) prepared by the present invention;

[0046] According to the adsorption curve, the adsorption-desorption curve of COF-366-Co-Bp (1.2 eq) is a type I isotherm curve, indicating that its structure is a microporous structure. The specific surface area of ​​the material is calculated to be 1588 m 2 g -1 , which is higher than the specific surface area of ​​COF-366-Co (1055m 2 g -1 ); According to the pore size distribution diagram, the pore size is mainly distributed at 1.95 nm, and the cumulative pore volume is 0.598 cm 3 / g; it is also higher than the cumulative pore volume of COF-366-Co (0.374 cm 3 / g); naturally, the specific surface area and cumulative pore volume of COF-366-Co-Bp (1.2eq) are much higher than those of the similar covalent organic framework - BpyCoTPP-DMTP-COF prepared by the reported preparation method.

[0047] Fig.10 This is a transmission electron microscope photo of the two-dimensional covalent organic framework -COF-366-Co;

[0048] The figure shows relatively obvious lattice fringes, with a crystal plane spacing of about 0.62nm.

[0049] Fig.11 This is a transmission electron microscope photo of the layered pillar type covalent organic framework - COF-366-Co-Pz (1.2eq) prepared by the present invention;

[0050] The figure shows obvious lattice fringes, and the interplanar spacing is about 1.43nm, which is much larger than the interplanar spacing of COF-366-Co (0.62nm).

[0051] Fig.12 This is a transmission electron microscope photo of the layered pillar type covalent organic framework - COF-366-Co-Bp (1.2eq) prepared by the present invention;

[0052] The figure shows obvious lattice fringes, and the interplanar spacing is about 1.75nm, which is much larger than the interplanar spacing of COF-366-Co (0.62nm).

[0053] Fig.13 The two-dimensional covalent organic framework-COF-366-Co in CO 2 Saturated, 0.1M KHCO 3In electrolyte, the scan rate is 5 mV·s -1 Linear sweep voltammetry curve (a) and the Faraday efficiency (FE) of electrocatalytic CO generation at potentials between -0.5V and -1.0V. CO %) curve graph (b);

[0054] From the voltammetric curve, we can see that when the potential is -1.20V, the current density is 24mA / cm 2 ; According to Faraday efficiency (FE CO %) curve, when the potential reaches -0.63V, its FE CO % reaches the highest point of 89.6%; when the potential continues to rise, FE CO % began to decline rapidly.

[0055] Fig.14 The layered columnar covalent organic framework-COF-366-Co-Pz (1.2 eq) prepared by the present invention is in CO 2 Saturated, 0.1M KHCO 3 In electrolyte, the scan rate is 5 mV·s -1 Linear sweep voltammetry curve (a) and the Faraday efficiency (FE) of electrocatalytic CO generation at potentials between -0.5V and -1.0V. CO %) curve graph (b);

[0056] From the voltammetric curve, we can see that when the potential is -1.20V, the current density is 27mA / cm 2 ; According to Faraday efficiency (FE CO %) curve, when the potential reaches -0.63V, its FE CO % reached the highest point of 90.3%, which was higher than that of COF-366-Co; and when the potential was between -0.63V and -0.74V, its FE CO % remains above 90%.

[0057] Fig.15 The layered pillar type covalent organic framework-COF-366-Co-Bp (1.2 eq) prepared by the present invention is in CO 2 Saturated, 0.1M KHCO 3 In electrolyte, the scan rate is 5 mV·s -1 Linear sweep voltammetry curve (a) and the Faraday efficiency (FE) of electrocatalytic CO generation at potentials between -0.5V and -1.0V. CO %) curve graph (b);

[0058] From the voltammetric curve, we can see that when the potential is -1.20V, the current density is 37mA / cm 2 According to the Faraday efficiency (FECO %) curve, when the potential reaches -0.63V, its FE CO % reached the highest point of 91.3%, which was higher than that of COF-366-Co; and when the potential was between -0.63V and -0.81V, its FE CO % remains above 90%. DETAILED DESCRIPTION

[0059] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention.

[0060] Example 1: A method for preparing a layered pillar type covalent organic framework material, the specific steps are as follows:

[0061] S1: 5,10,15,20-tetrakis(4-aminophenyl)porphyrin-cobalt (TAPP-Co, 18 mg, 0.025 mmol), terephthalaldehyde (10 mg, 0.075 mmol) and Pz (2.4 mg, 0.03 mmol, 1.2 eq) were placed in an ampoule with a volume of 10 mL, 0.25 mL of n-butanol and 0.25 mL of o-dichlorobenzene were added, and the raw materials were evenly dispersed by ultrasound; then, a pre-prepared aqueous solution of scandium trifluoromethanesulfonate catalyst (9.1 mg dissolved in 65 uL of water, 0.284 mol / L) was added;

[0062] S2: The mixed system was subjected to liquid nitrogen freezing and vacuum degassing treatment for three times in sequence, and the ampoule was sealed by baking with a flame gun under vacuum, and then placed in a 120° C. oven for reaction for 2 days to obtain a crude product;

[0063] S3: The crude product was washed with water and acetone by filtration, and then extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively. After vacuum drying at 65°C for 12 hours, 17 mg of purple-red solid powder was obtained with a yield of 56.7%, which was recorded as COF-366-Co-Pz (1.2 eq).

[0064] The powder X-ray diffraction pattern of the layered columnar covalent organic framework-COF-366-Co-Pz (1.2 eq) prepared in this example is as follows Figure 3 As shown in (a), COF-366-Co-Pz (1.2 eq) has a high degree of crystallinity. Among them, 3.44, 4.17, 6.88 and 8.38 degrees are characteristic peaks of the material, and the strongest peak is located at 3.44 degrees, with a diffraction intensity of about 3004, which is much higher than COF-366-Co (1130, such as Figure 2).like Figure 7 The nitrogen adsorption-desorption curve (a) and pore size distribution diagram (b) of COF-366-Co-Pz (1.2 eq) prepared in this example are shown in FIG. Figure 7 (a) It can be seen that the adsorption-desorption curve of COF-366-Co-Pz (1.2 eq) is a type I isotherm curve, indicating that its structure is a microporous structure. The specific surface area of ​​the material is calculated to be 1970 m 2 g -1 , much higher than the specific surface area of ​​COF-366-Co (1055m 2 g -1 ,like Figure 6 (a)); According to the pore size distribution diagram in 7(b), the pore sizes are mainly distributed at 1.24 nm and 1.78 nm, and the cumulative pore volume is 0.741 cm 3 / g; it is also much higher than the cumulative pore volume of COF-366-Co (0.391cm 3 / g, such as Figure 6 (b)). Fig.11 The transmission electron microscope image of COF-366-Co-Pz (1.2 eq) prepared in the example shows obvious lattice fringes with a spacing of about 1.43 nm, which is much larger than the interplanar spacing of COF-366-Co (0.62 nm, as shown in FIG. Fig.10 ).like Fig.14 COF-366-Co-Pz (1.2eq) in CO 2 Saturated, 0.1M KHCO 3 In electrolyte, the scan rate is 5 mV·s -1 Linear sweep voltammetry curves under -0.5V~-1.0V and the Faraday efficiency (FE) of electrocatalytic generation of CO CO %) curve; From 14 (a) volt-ampere curve, when the potential is -1.20V, the current density is 27mA / cm 2 , higher than COF-366-Co (24mA / cm 2 ,like Fig.13 (a)); according to 14(b) Faraday efficiency (FE CO %) curve, when the potential reaches -0.63V, its FE CO % reached the highest point of 90.3%, compared with COF-366-Co(FE CO %=89.6%) is improved; and when the potential is between -0.63V~-0.74V, its FE CO % still maintained above 90%, while that of COF-366-Co decreased rapidly with the increase of potential.

[0065] Example 2: A method for preparing a layered pillar type covalent organic framework material, the specific steps are as follows:

[0066] S1: Place TAPP-Co (18 mg, 0.025 mmol), terephthalaldehyde (10 mg, 0.075 mmol) and Bp (4.68 mg, 0.03 mmol, 1.2 eq) in an ampoule with a volume of 10 mL, add 0.25 mL of n-butanol and 0.25 mL of o-dichlorobenzene, and disperse the raw materials evenly by ultrasound; then add the prepared scandium trifluoromethanesulfonate catalyst aqueous solution (9.1 mg dissolved in 65 uL of water, 0.284 mol / L);

[0067] S2: The mixed system was subjected to liquid nitrogen freezing and vacuum degassing treatment for three times in sequence, and the ampoule was sealed by baking with a flame gun under vacuum, and then placed in a 120° C. oven for reaction for 2 days to obtain a crude product;

[0068] S3: The crude product was washed with water and acetone by filtration, and then extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively. After vacuum drying at 65°C for 12 hours, 18 mg of purple-red solid powder was obtained with a yield of 55%, which was recorded as COF-366-Co-Bp (1.2 eq).

[0069] The powder X-ray diffraction pattern of the layered columnar covalent organic framework-COF-366-Co-Bp (1.2 eq) prepared in this example is as follows Figure 5 As shown in (a), COF-366-Co-Bp (1.2 eq) has a high degree of crystallinity. Among them, 3.48, 4.01, 6.96 and 10.09 degrees are characteristic peaks of the material; its strongest peak is located at 3.48 degrees, and the diffraction intensity is about 1296, which is slightly higher than COF-366-Co (1130, such as Figure 2 ), indicating that the crystallinity of the material has been slightly enhanced after the introduction of Bp. Figure 4 It can be clearly seen that the covalent organic framework - Bpy CoTPP-DMTP-COF prepared by introducing Bpy using the method reported in the literature has a significantly lower crystallinity than the covalent organic framework - CoTPP-DMTP-COF without introducing Bpy; this also shows that the preparation method of the present invention is superior to the preparation method reported in the literature. Fig. 9 The nitrogen adsorption-desorption curve (a) and pore size distribution diagram (b) of COF-366-Co-Bp (1.2 eq) prepared in this example are shown in FIG. Fig. 9 (a) It can be seen that the adsorption-desorption curve of COF-366-Co-Bp (1.2 eq) is a type I isotherm curve, indicating that its structure is a microporous structure. The specific surface area of ​​the material is calculated to be 1599 m 2 g -1, which is higher than the specific surface area of ​​COF-366-Co (1055m 2 g -1 ,like Figure 6 (a)); According to the pore size distribution diagram in 9(b), the pore size is mainly distributed at 1.95 nm, and the cumulative pore volume is 0.598 cm 3 / g; it is also much higher than the cumulative pore volume of COF-366-Co (0.391cm 3 / g, such as Figure 6 (b)). Figure 8 It is shown that the specific surface area and cumulative pore volume of the covalent organic framework-Bpy CoTPP-DMTP-COF prepared according to the reported method are lower than the specific surface area and cumulative pore volume of the covalent organic framework-CoTPP-DMTP-COF without the introduction of Bpy; and the specific surface area and cumulative pore volume of CoTPP-DMTP-COF are lower than the specific surface area and cumulative pore volume of COF-366-Co; therefore, the specific surface area and cumulative pore volume of CoTPP-DMTP-COF are also lower than the specific surface area and cumulative pore volume of COF-366-Co-Bp (1.2eq). Fig.12 The transmission electron microscope image of COF-366-Co-Bp (1.2 eq) prepared in the embodiment shows obvious lattice fringes with a spacing of about 1.75 nm, which is much larger than the interplanar spacing of COF-366-Co (0.62 nm, as shown in FIG. Fig.10 ).like Fig.15 COF-366-Co-Bp (1.2 eq) in CO 2 Saturated, 0.1M KHCO 3 In electrolyte, the scan rate is 5 mV·s -1 Linear sweep voltammetry curves under -0.5V~-1.0V and the Faraday efficiency (FE) of electrocatalytic generation of CO CO %) curve; From 15 (a) volt-ampere curve, when the potential is -1.20V, the current density is 37mA / cm 2 , higher than COF-366-Co (24mA / cm 2 ,like Fig.13 (a)); according to 15(b) Faraday efficiency (FE CO %) curve, when the potential reaches -0.63V, its FE CO % reached the highest point of 91.3%, compared with COF-366-Co(FE CO %=89.6%) is improved; and when the potential is between -0.63V~-0.80V, its FE CO % still maintained above 90%, while that of COF-366-Co decreased rapidly with the increase of potential.

[0070] The Bpy CoTPP-DMTP-COF and CoTPP-DMTP-COF can be found in Angew. Chem. Int. Ed. 2024, DOI: 10.1002 / anie.202416771 and 2. J. Am. Chem. Soc. 2024, 146, 32640.

[0071] Embodiment 3: The preparation method of the layered pillar type covalent organic framework of the present invention, the specific steps are as follows:

[0072] S1: Place TAPP-Co (18 mg, 0.025 mmol), terephthalaldehyde (10 mg, 0.075 mmol) and Pz (4 mg, 0.05 mmol, 2 eq) in an ampoule with a volume of 10 mL, add 0.25 mL of n-butanol and 0.25 mL of o-dichlorobenzene, and disperse the raw materials evenly by ultrasound; then add the prepared scandium trifluoromethanesulfonate catalyst aqueous solution (9.1 mg dissolved in 65 uL of water, 0.284 mol / L);

[0073] S2: The mixed system was subjected to liquid nitrogen freezing and vacuum degassing treatment for three times in sequence, and the ampoule was sealed by baking with a flame gun under vacuum, and then placed in a 120° C. oven for reaction for 2 days to obtain a crude product;

[0074] S3: The crude product was washed with water and acetone by filtration, and then extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively. After vacuum drying at 65°C for 12 hours, 16.8 mg of purple-red solid powder was obtained with a yield of 56.5%, which was recorded as COF-366-Co-Pz1 (2 eq).

[0075] The powder X-ray diffraction pattern of the layered columnar covalent organic framework-COF-366-Co-Pz1 (2 eq) prepared in this example is as follows Figure 3 As shown in (b), the strongest peak diffraction intensity of COF-366-Co-Pz1 (2 eq) is about 1090 and the strongest peak diffraction intensity of COF-366-Co (1130, Figure 2 ) is close; this also shows that as the Pz equivalent increases, the crystallinity of the layered pillar type covalent organic framework decreases, and may even be lower than the crystallinity of COF-366-Co. Other tests and characterizations are basically consistent with Examples 1 and 2.

[0076] Example 4: The preparation method of the layered pillar type covalent organic framework of the present invention, the specific steps are as follows:

[0077] S1: Place TAPP-Co (18 mg, 0.025 mmol), terephthalaldehyde (10 mg, 0.075 mmol) and Bp (11.7 mg, 0.075 mmol, 3 eq) in an ampoule with a volume of 10 mL, add 0.25 mL of n-butanol and 0.25 mL of o-dichlorobenzene, and disperse the raw materials evenly by ultrasound; then add the prepared scandium trifluoromethanesulfonate catalyst aqueous solution (9.1 mg dissolved in 65 uL of water, 0.284 mol / L);

[0078] S2: The mixed system was subjected to liquid nitrogen freezing and vacuum degassing treatment for three times in sequence, and the ampoule was sealed by baking with a flame gun under vacuum, and then placed in a 120° C. oven for reaction for 2 days to obtain a crude product;

[0079] S3: The crude product was washed with water and acetone by filtration, and then extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively. After vacuum drying at 65°C for 12 hours, 18 mg of purple-red solid powder was obtained with a yield of 55%, which was recorded as COF-366-Co-Bp1 (3 eq).

[0080] The powder X-ray diffraction pattern of the layered columnar covalent organic framework-COF-366-Co-Bp1 (3 eq) prepared in this example is as follows: Figure 5 As shown in (b), it is shown that the strongest peak diffraction intensity of COF-366-Co-Bp1 (3 eq) is about 956, which is lower than the strongest peak diffraction intensity of COF-366-Co (1130, Figure 2 ), which also shows that as the Bp equivalent increases, the crystallinity of the layered pillar type covalent organic framework decreases, and may even be lower than the crystallinity of COF-366-Co. Other tests and characterizations are basically consistent with Examples 1 and 2.

[0081] Example 5: The preparation method of the layered pillar type covalent organic framework of the present invention, the specific steps are as follows:

[0082] S1: Place TAPP-Co (18 mg, 0.025 mmol), 2,5-dimethylterephthalaldehyde (12.2 mg, 0.075 mmol) and Pz (2.4 mg, 0.03 mmol) in an ampoule with a volume of 10 mL, add 0.25 mL of n-butanol and 0.25 mL of o-dichlorobenzene, and disperse the raw materials evenly by ultrasound; then add the prepared scandium trifluoromethanesulfonate catalyst aqueous solution (9.1 mg dissolved in 65 uL of water, 0.284 mol / L);

[0083] S2: The mixed system was subjected to liquid nitrogen freezing and vacuum degassing treatment for three times in sequence, and the ampoule was sealed by baking with a flame gun under vacuum, and then placed in a 120° C. oven for reaction for 2 days to obtain a crude product;

[0084] S3: The crude product was washed with water and acetone by filtration, and then extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively. After vacuum drying at 65°C for 12 hours, 17.2 mg of purple-red solid powder was obtained with a yield of 56.4%, which was recorded as COF-366-Co-Pz2.

[0085] The testing and characterization of the layered columnar covalent organic framework - COF-366-Co-Pz2 prepared in this example are basically consistent with those of Example 1 and Example 2.

[0086] Example 6: The preparation method of the layered pillar type covalent organic framework of the present invention, the specific steps are as follows:

[0087] S1: Place TAPP-Co (18 mg, 0.025 mmol), 2,5-dimethylterephthalaldehyde (12.2 mg, 0.075 mmol) and Bp (4.68 mg, 0.03 mmol) in an ampoule with a volume of 10 mL, add 0.25 mL of n-butanol and 0.25 mL of o-dichlorobenzene, and disperse the raw materials evenly by ultrasound; then add the prepared scandium trifluoromethanesulfonate catalyst aqueous solution (9.1 mg dissolved in 65 uL of water, 0.284 mol / L);

[0088] S2: The mixed system was subjected to liquid nitrogen freezing and vacuum degassing treatment for three times in sequence, and the ampoule was sealed by baking with a flame gun under vacuum, and then placed in a 120° C. oven for reaction for 2 days to obtain a crude product;

[0089] S3: The crude product was washed with water and acetone by filtration, and then extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively. After vacuum drying at 65°C for 12 hours, 18.5 mg of purple-red solid powder was obtained with a yield of 54.7%, which was recorded as COF-366-Co-Bp2.

[0090] The testing and characterization of the layered columnar covalent organic framework - COF-366-Co-Bp2 prepared in this example are basically consistent with those in Example 1 and Example 2.

[0091] Embodiment 7: The preparation method of the layered pillar type covalent organic framework of the present invention, the specific steps are as follows:

[0092] S1: Place TAPP-Co (18 mg, 0.025 mmol), terephthalaldehyde (10 mg, 0.075 mmol) and TPA (5.0 mg, 0.03 mmol) in an ampoule with a volume of 10 mL, add 0.25 mL of n-butanol and 0.25 mL of o-dichlorobenzene, and disperse the raw materials evenly by ultrasound; then add the prepared scandium trifluoromethanesulfonate catalyst aqueous solution (9.1 mg dissolved in 65 uL of water, 0.284 mol / L);

[0093] S2: The mixed system was subjected to liquid nitrogen freezing and vacuum degassing treatment for three times in sequence, and the ampoule was sealed by baking with a flame gun under vacuum, and then placed in a 120° C. oven for reaction for 2 days to obtain a crude product;

[0094] S3: The crude product was washed with water and acetone by filtration, and then extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively. After vacuum drying at 65°C for 12 hours, 15 mg of purple-red solid powder was obtained with a yield of 45.4%, which was recorded as COF-366-Co-TPA.

[0095] The testing and characterization of the layered pillar covalent organic framework - COF-366-Co-TPA prepared in this example are basically consistent with those in Example 1 and Example 2.

[0096] Embodiment 8: The preparation method of the layered pillar type covalent organic framework of the present invention comprises the following specific steps:

[0097] S1: Place TAPP-Co (18 mg, 0.025 mmol), 2,5-dimethylterephthalaldehyde (12.2 mg, 0.075 mmol) and TPA (5.0 mg, 0.03 mmol) in an ampoule with a volume of 10 mL, add 0.25 mL of n-butanol and 0.25 mL of o-dichlorobenzene, and disperse the raw materials evenly by ultrasound; then add the prepared scandium trifluoromethanesulfonate catalyst aqueous solution (9.1 mg dissolved in 65 uL of water, 0.284 mol / L);

[0098] S2: The mixed system was subjected to liquid nitrogen freezing and vacuum degassing treatment for three times in sequence, and the ampoule was sealed by baking with a flame gun under vacuum, and then placed in a 120° C. oven for reaction for 2 days to obtain a crude product;

[0099] S3: The crude product was washed with water and acetone by filtration, extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively, and dried under vacuum at 65°C for 12 hours to obtain 17 mg of purple-red solid powder with a yield of 48.5%, recorded as COF-366-Co-TPA1.

[0100] The testing and characterization of the layered pillar covalent organic framework - COF-366-Co-TPA1 prepared in this example are basically consistent with those of Example 1 and Example 2.

[0101] Example 9: The preparation method of the layered pillar type covalent organic framework of the present invention, the specific steps are as follows:

[0102] S1: Place TAPP-Co (18 mg, 0.025 mmol), terephthalaldehyde (10 mg, 0.075 mmol) and Pz (2 mg, 0.025 mmol) in an ampoule with a volume of 10 mL, add 0.25 mL of n-butanol and 0.25 mL of o-dichlorobenzene, and disperse the raw materials evenly by ultrasound; then add the prepared scandium trifluoromethanesulfonate catalyst aqueous solution (9.1 mg dissolved in 65 uL of water, 0.284 mol / L);

[0103] S2: The mixed system was subjected to liquid nitrogen freezing and vacuum degassing treatment for three times in sequence, and the ampoule was sealed by baking with a flame gun under vacuum, and then placed in a 120° C. oven for reaction for 2 days to obtain a crude product;

[0104] S3: The crude product was washed with water and acetone by filtration, extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively, and dried under vacuum at 65°C for 12 hours to obtain 16.8 mg of purple solid powder with a yield of 56.5%, recorded as COF-366-Co-Pz3.

[0105] The testing and characterization of the layered columnar covalent organic framework - COF-366-Co-Pz3 prepared in this example are basically consistent with those in Example 1 and Example 2.

[0106] Embodiment 10: The preparation method of the layered pillar type covalent organic framework of the present invention, the specific steps are as follows:

[0107] S1: Place TAPP-Co (18 mg, 0.025 mmol), terephthalaldehyde (10 mg, 0.075 mmol) and Pz (2.4 mg, 0.03 mmol) in an ampoule with a volume of 10 mL, add 0.25 mL of n-butanol and 0.25 mL of o-dichlorobenzene, and disperse the raw materials evenly by ultrasound; then add the prepared aqueous solution of zinc trifluoromethanesulfonate catalyst (6.7 mg dissolved in 65 uL of water, 0.284 mol / L);

[0108] S2: The mixed system was subjected to liquid nitrogen freezing and vacuum degassing treatment for three times in sequence, and the ampoule was sealed by baking with a flame gun under vacuum, and then placed in a 120° C. oven for reaction for 2 days to obtain a crude product;

[0109] S3: The crude product was washed with water and acetone by filtration, extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively, and dried under vacuum at 65°C for 12 hours to obtain 17 mg of purple-red solid powder with a yield of 56.7%, recorded as COF-366-Co-Pz4.

[0110] The testing and characterization of the layered pillar covalent organic framework - COF-366-Co-Pz4 prepared in this example are basically consistent with those in Example 1 and Example 2.

[0111] Embodiment 11: The preparation method of the layered pillar type covalent organic framework of the present invention, the specific steps are as follows:

[0112] S1: Place TAPP-Co (18 mg, 0.025 mmol), terephthalaldehyde (10 mg, 0.075 mmol) and Pz (2.4 mg, 0.03 mmol) in an ampoule with a volume of 10 mL, add 0.25 mL of n-butanol and 0.25 mL of o-dichlorobenzene, and disperse the raw materials evenly by ultrasound; then add the prepared scandium trifluoromethanesulfonate catalyst aqueous solution (5.8 mg dissolved in 130 uL of water, 0.09 mol / L);

[0113] S2: The mixed system was subjected to liquid nitrogen freezing and vacuum degassing treatment for three times in sequence, and the ampoule was sealed by baking with a flame gun under vacuum, and then placed in a 120° C. oven for reaction for 2 days to obtain a crude product;

[0114] S3: The crude product was washed with water and acetone by filtration, extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively, and dried under vacuum at 65°C for 12 hours to obtain 12.6 mg of purple solid powder with a yield of 42%, recorded as COF-366-Co-Pz5.

[0115] The testing and characterization of the layered pillar covalent organic framework - COF-366-Co-Pz5 prepared in this example are basically consistent with those in Example 1 and Example 2.

[0116] Example 12: The preparation method of the layered pillar type covalent organic framework of the present invention, the specific steps are as follows:

[0117] S1: 5,10,15,20-tetrakis(4-aminophenyl)porphyrin-copper (TAPP-Cu, 18.2 mg, 0.025 mmol), terephthalaldehyde (10 mg, 0.075 mmol) and Pz (2.4 mg, 0.03 mmol) were placed in an ampoule with a volume of 10 mL, 0.25 mL of n-butanol and 0.25 mL of o-dichlorobenzene were added, and the raw materials were evenly dispersed by ultrasound; then, a pre-prepared aqueous solution of scandium trifluoromethanesulfonate catalyst (5.8 mg dissolved in 130 uL of water, 0.09 mol / L) was added;

[0118] S2: The mixed system was subjected to liquid nitrogen freezing and vacuum degassing treatment for three times in sequence, and the ampoule was sealed by baking with a flame gun under vacuum, and then placed in a 120° C. oven for reaction for 2 days to obtain a crude product;

[0119] S3: The crude product was washed with water and acetone by filtration, and then extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively. After vacuum drying at 65°C for 12 hours, 12.6 mg of purple solid powder was obtained with a yield of 42%, which was recorded as COF-366-Cu-Pz.

[0120] The testing and characterization of the layered pillar covalent organic framework - COF-366-Cu-Pz prepared in this example are basically consistent with those in Example 1 and Example 2.

[0121] Example 13: The preparation method of the layered pillar type covalent organic framework of the present invention, the specific steps are as follows:

[0122] S1: Place TAPP-Co (18 mg, 0.025 mmol), terephthalaldehyde (10 mg, 0.075 mmol) and 4,4'-(2,5-dimethyl-1,4-phenylene) dipyridine (DPP) (7.8 mg, 0.03 mmol) in an ampoule with a volume of 10 mL, add 0.25 mL of n-butanol and 0.25 mL of o-dichlorobenzene, and disperse the raw materials evenly by ultrasound; then add the prepared scandium trifluoromethanesulfonate catalyst aqueous solution (9.1 mg dissolved in 65 uL of water, 0.284 mol / L);

[0123] S2: The mixed system was subjected to liquid nitrogen freezing and vacuum degassing treatment for three times in sequence, and the ampoule was sealed by baking with a flame gun under vacuum, and then placed in a 120° C. oven for reaction for 2 days to obtain a crude product;

[0124] S3: The crude product was washed with water and acetone by filtration, and then extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively. After vacuum drying at 65°C for 12 hours, 15.6 mg of purple-black solid powder was obtained with a yield of 42%, which was recorded as COF-366-Co-DPP.

[0125] The testing and characterization of the layered pillar type covalent organic framework - COF-366-Co-DPP prepared in this example are basically consistent with those in Example 1 and Example 2.

[0126] Example 14: The preparation method of the layered pillar type covalent organic framework of the present invention, the specific steps are as follows:

[0127] S1: 5,10,15,20-tetrakis(4-formylphenyl)porphyrin-cobalt (TFPP-Co, 19.5 mg, 0.025 mmol), p-phenylenediamine (8.1 mg, 0.075 mmol) and Pz (2.4 mg, 0.03 mmol) were placed in an ampoule with a volume of 10 mL, 0.25 mL of n-butanol and 0.25 mL of o-dichlorobenzene were added, and the raw materials were evenly dispersed by ultrasound; then, a pre-prepared aqueous solution of scandium trifluoromethanesulfonate catalyst (9.1 mg dissolved in 65 uL of water, 0.284 mol / L) was added;

[0128] S2: The mixed system was subjected to liquid nitrogen freezing and vacuum degassing treatment for three times in sequence, and the ampoule was sealed by baking with a flame gun under vacuum, and then placed in a 120° C. oven for reaction for 2 days to obtain a crude product;

[0129] S3: The crude product was washed with water and acetone by filtration, extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively, and dried under vacuum at 65°C for 12 hours to obtain 16 mg of purple-red solid powder with a yield of 55%, recorded as COF-366-Co-Pz6.

[0130] The testing and characterization of the layered columnar covalent organic framework - COF-366-Co-Pz6 prepared in this example are basically consistent with those in Example 1 and Example 2.

Claims

1. A layered columnar covalent organic framework material, the structural formula of which is as follows: in, X or Y is C or N, X and Y are different; M is a transition metal; for Ar or Ar' is one of the following: R is an alkyl group or an alkoxy group.

2. A layered pillar type covalent organic framework material as claimed in claim 1, characterized in that The transition metal is Co, Fe or Cu.

3. A layered pillar type covalent organic framework material as claimed in claim 1, characterized in that The alkyl or alkoxy group is H, CH з , C2H5, OH or OMe.

4. The method for preparing a layered pillar type covalent organic framework material according to claim 1, characterized in that The method comprises the following steps: Step 1, M-Por, aromatic dialdehyde or aromatic diamine, and pillaring molecules are mixed at a molar ratio of 1:2:1-2 to make the concentration of M-Por 0.05M, and then n-butanol and o-dichlorobenzene are added, and after ultrasonic dispersion, a catalyst is added; Step 2, the mixed system of step 1 is sequentially frozen with liquid nitrogen, vacuumed and degassed, and then the system is sealed to obtain a crude product; Step 3, the crude product is filtered, washed, extracted with Soxhlet, and vacuum dried to obtain a columnar covalent organic framework material; The M-Por is TAPP or TFPP.

5. The method for preparing a layered pillar type covalent organic framework material according to claim 2, characterized in that The catalyst is Lewis acid, namely trifluoromethanesulfonic acid metal salt, including scandium trifluoromethanesulfonate, zinc trifluoromethanesulfonate, iron trifluoromethanesulfonate, yttrium trifluoromethanesulfonate and indium trifluoromethanesulfonate, and the concentration thereof is 0.09-0.3 mol / L.

6. A method for preparing a layered pillar type covalent organic framework material as claimed in claim 2, characterized in that The volume ratio of the n-butanol to o-dichlorobenzene mixture is 1:

1.

7. The method for preparing a layered pillar type covalent organic framework material according to claim 2, characterized in that The crude product was washed by filtration with water and acetone, extracted with 1,4-dioxane and acetone Soxhlet for 24 hours respectively, and dried under vacuum at 65° C. for 12 hours to obtain a columnar covalent organic framework material.

8. The layered pillar type covalent organic framework material as claimed in claim 1 is used for electrocatalytic reduction of carbon dioxide.

Citation Information

Patent Citations

  • Covalent organic framework with triphenylphosphine as framework as well as preparation method and application of covalent organic framework

    CN109762180A

  • Cobalt porphyrin-based porous organic polymer as well as preparation method and application thereof

    CN117510764A

  • Green and efficient method for producing benzaldehyde through catalytic oxidation of benzyl alcohol

    CN117820093A